Paleoclimatic and vegetational change in the Siwalik sub-Group of Pakistan and its contemporary geographic regions: a stable isotope perspective. Issue 7 (3rd October 2021) - Waseem, M. T.; Khan, A. M.; Quade, J.; Nelson, S. Von
Abstract: Paleoclimatic archives preserved in bioapatite provide long-term temporal records of climatic change and allow us to explore how climate may have affected faunal and floral changes through time. Among the most comprehensively debated research questions is the question of C4 grassland expansion and its effects on community structure and dynamics. Here, we present compiled datasets of carbon isotopes from fossil tooth enamel and paleosol to evaluate how C4 grasslands expanded and its apparent causes. The C4 expansion has been argued to be around ca 8–7 Ma in the Siwalik sub-Group of Pakistan, but the later stages of C3 /C4 proportion shifts on the Siwalik floodplains are less understood. We found that although C4 expansion occurred during the late Miocene, C3 vegetation never entirely disappeared but was persisted in pockets on floodplain up to the present, as indicated by the C3 diet consumed by some herbivores. The expansion was further modulated by the microclimate in different regions. The same scenario can be seen in East Africa, South America and low-latitude North America where C4 grasslands expanded rapidly in late Miocene most likely owing to decrease in global p CO2 . By contrast, C4 plants did not expand in high-latitude North America and Palearctic regions during the past ca 17 Ma. Thus, we assume that C4 plants expanded at low latitudes during the late Miocene owing to one major global factor (decreased p CO2 ) and perhaps other local microclimatic factors like paleofires. KEY POINTS: During the late Miocene, low-latitude regions experienced a climatic change followed by a transition from C3 to C4 vegetation. The timing of C4 expansion was not synchronous across all the regions and was controlled by global and microclimatic factors. Although C4 vegetation expanded after the late Miocene, C3 vegetation did not disappear and was present at the edges of floodplains. The new adaptive physiologies (like hypsodonty) in faunal elements were evolutionary adaptive responses toward new vegetational types available.